Basin-scale control on N2O loss rate and emission in the Changjiang River network, China - Wang, Fang; Yu, Qibiao; Yan, Weijin; Tian, Siyu; Zhang, Peipei; Wang, Jianing (Frontiers in Marine Science, 2022)
Global riverine N2O emissions have been made by several studies with great uncertainty. However, the regional N2O budgets and patterns in large river networks is still unclear, due to the lacking understanding of in-river N2O emission rate and well-classified river network water areas. Furthermore, the mass ratio of N2O emission against nitrogen(N) load in river networks remains controversial. Here we report N2O emissions from the largest river of China, the Changjiang River network, emphasizing the basin-scale control on riverine N2O loss rate in response to increasing N loads and river size. We find the N2O emission rate is negatively related to Strahler river orders, and positively related to N loading. The velocity (Vf) of N conversion into N2O was 0.131-0.436 m yr-1, and N2O loss rate (ζ) was 0.27-37.64 ×10-4 d-1 and declined exponentially with water discharge. Both the loss rate and the mass ratio of N conversion into N2O varied significantly at basin scale, indicating the diminishing capacity of river ecosystems to convert excess DIN into N2O when N load increased as a direct result of human activities. Our study shows N2O emission was 0.66 Gg N2O-N (1Gg=109g) in 1986 and increased to 10.3 Gg N2O-N in 2014 for the whole Changjiang River network. We identified the headwater streams are hotspots of N2O emission across the headwater stream to the estuary aquatic continuum. N2O emission was about 0.82% - 5.31% of global riverine N2O budget during 2010-2014. Our study suggested that an integrated approach in view of the riverine N loads and river hydrology is needed to improve estimates of riverine N2O emissions.